More or Less Maddy - Genova, Lisa ([Place of publication not identified] : Gallery/Scout Press, 2025)
A ... novel about a young woman diagnosed with bipolar disorder who rejects the stability and approval found in a traditionally "normal" life for a career in stand-up comedy. Maddy Banks is just like any other stressed-out freshman at NYU. Between schoolwork, exams, navigating life in the city, and a recent breakup, it's normal to be feeling overwhelmed. It doesn't help that she's always felt like the odd one out in her picture-perfect Connecticut family. But Maddy's latest low is devastatingly low, and she goes on an antidepressant. She begins to feel good, dazzling in fact, and she soon spirals high into a wild and terrifying mania that culminates in a diagnosis of bipolar disorder. As she struggles to find her way in this new reality, navigating the complex effects bipolar has on her identity, her relationships, and her life dreams, Maddy will have to figure out how to manage being both too much and not enough.
New book 2025 winter.
Keywords: Stand-up comedy; People with bipolar disorder; Young women; Novels; College students; Families; Neurodiversity; Connecticut